Experimental evaluation of Hingusauvarchaladi Ghrita and Saptavartita Hingusauvarchaladi Ghrita with special reference to their anticonvulsant activity - Roshy, Joseph C. (Medknow Publications Pvt Ltd, 2010)
Incidence of epilepsy is 0.3 to 0.5% in different populations throughout the world, and the prevalence of epilepsy has been estimated at 5 to 10 persons per 1000. Scanning of the Ayurvedic classics reveals that 90% of the formulations mentioned to have action on sajnavaha srotas are ghrita-based formulations. Ghrita because of its yogavahi guna, incorporates the qualities of the drugs added to it without losing its own qualities. In the present study Hingusauvarchaladi ghrita and saptavartita Hingusauvarchaladi ghrita have been selected, to prove their anticonvulsant activity experimentally on albino mice, by the chemoshock method. The observations recorded have been analyzed by one-way ANOVA followed by Scheffe's test, statistically. Saptavartita Hingusauvarchaladi ghrita has shown better anticonvulsant activity in comparison to Hingusauvarchaladi ghrita.